Comparison of photosynthetic activity and heat tolerance between near isogenic lines of wheat with different photosynthetic rates. - Chongyang Li; Mingyang Ma; Tianpeng Zhang; Pengwen Feng; Xiao Chen; Yang Liu; Marian Brestic; Tarek M Galal; Hatim M Al-Yasi; Xinghong Yang (PLoS ONE)
Wheat (Triticum aestivum L.) is one of the most important crops in the world, but the yield and quality of wheat are highly susceptible to heat stress, especially during the grain-filling stage. Therefore, it is crucial to select high-yield and high-temperature-resistant varieties for food cultivation. There is a positive correlation between the yield and photosynthetic rate of wheat during the entire grain-filling stage, but few studies have shown that lines with high photosynthetic rates can maintain higher thermotolerance at the same time. In this study, two pairs of wheat near isogenic lines (NILs) with different photosynthetic rates were used for all experiments. Our results indicated that under heat stress, lines with a high photosynthetic rate could maintain the activities of photosystem II (PSII) and key Calvin cycle enzymes in addition to their higher photosynthetic rates. The protein levels of D1 and HSP70 were significantly increased in the highly photosynthetic lines, which contributed to maintaining high photosynthetic rates and ensuring the stability of the Calvin cycle under heat stress. Furthermore, we found that lines with a high photosynthetic rate could maintain high antioxidant enzyme activity to scavenge reactive oxygen species (ROS) and reduce ROS accumulation better than lines with a low photosynthetic rate under high-temperature stress. These findings suggest that lines with high photosynthetic rates can maintain a higher photosynthetic rate despite heat stress and are more thermotolerant than lines with low photosynthetic rates.